2006
DOI: 10.1002/bsl.739
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the validity of anger regulation problems, interpersonal style, and disturbed mental state for predicting inpatient violence

Abstract: Research has been conducted to try to identify risk factors to help predict which patients will be violent during psychiatric hospitalization. Despite the relatively large amount of research conducted, it is difficult to draw any firm conclusions, as the studies vary considerably in study design, methods used, and choice of outcome measures. Studies also tend to focus on risk prediction, even though risk management is the primary aim of clinical practice in mental health services and few studies have focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 45 publications
10
75
2
Order By: Relevance
“…Again these results are not surprising, given that the most common type of aggression exhibited in our facility is impulsive. This finding is consistent with other research in the area of risk assessment for institutional aggression, which has shown both anger and psychiatric symptoms to be robust predicators of such aggression (Cornell, Peterson, & Richards, 1999;Doyle & Dolan, 2006;Nijman, à Campo, Ravelli, & Merckelbach, 1999;Ogloff & Daffern, 2006). These findings suggest that treatment programs designed to ameliorate psychiatric symptoms and decrease anger may be most useful in the management of institutional aggression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Again these results are not surprising, given that the most common type of aggression exhibited in our facility is impulsive. This finding is consistent with other research in the area of risk assessment for institutional aggression, which has shown both anger and psychiatric symptoms to be robust predicators of such aggression (Cornell, Peterson, & Richards, 1999;Doyle & Dolan, 2006;Nijman, à Campo, Ravelli, & Merckelbach, 1999;Ogloff & Daffern, 2006). These findings suggest that treatment programs designed to ameliorate psychiatric symptoms and decrease anger may be most useful in the management of institutional aggression.…”
Section: Discussionsupporting
confidence: 91%
“…In meteorological science, not only is a weather event predicted; specific time parameters are included in this prediction. In inpatient facilities, imminent aggression is of substantially more interest than long-term outcomes (Doyle & Dolan, 2006;Hoptman, Yates, Patalinjug, Wack, & Convit, 1999;Linaker & Busch-Iversen, 1995;McNiel & Binder, 1995). Identifying which patients are likely to exhibit aggressive behavior while in the institution is more relevant for individuals managing such patients.…”
mentioning
confidence: 97%
“…Assessment of interpersonal style using these tools shows good interrater reliability (Blackburn 1998;Kiesler 2006) and research has suggested that interpersonal style can indeed add to the predictive validity of violence risk assessment, at least in institutional settings. A study that used the CIRCLE to evaluate forensic inpatients (predominantly with psychotic illnesses) found that dominant, hostile and coercive interpersonal styles were associated with a higher risk of violent behaviour over the following 3 months, whereas a compliant interpersonal style was protective against subsequent violence (Doyle 2006). Another forensic inpatient study using the CIRCLE (Daffern 2010a) found that a coercive interpersonal style was associated with increased risk of aggression and selfharm during the following 6 months.…”
Section: Interpersonal Dynamics In Therapeutic Relationshipsmentioning
confidence: 99%
“…The assessment of anger can contribute to an understanding of impulsivity, which is identified as a risk factor in instruments such as the HistoricalClinical-Risk Management-20 assessment protocol (Douglas, Hart, Webster, Belfrage, & Eaves, 2008). Doyle and Dolan (2006) suggest that measures such as the HCR-20 "might not be best suited to routine clinical use in acute settings, where assessments need to be made quickly with little or no background information" (p. 784). In their study, they found that staff-rated patient anger over the previous week was higher for patients who were subsequently (over the 12-week study period) physically violent or who threatened violence, and that the measure they used to assess anger was predictive of patients who were violent/threatened violence controlling for factors such as gender, age, and presence of major mental disorder.…”
Section: Implications For Clinical Forensic Nursing Practicementioning
confidence: 99%
“…Although anger need not be a contributing factor in all acts of aggression (Howells, 2004), its association with violence provides a strong rationale for its assessment (Doyle & Dolan, 2006). Indeed, anger management is a common component of violence reduction programs, with one evaluation by Dowden and Andrews (2000) reporting that violence programs which targeted negative affect/anger were more effective in reducing re-offending.…”
Section: Introductionmentioning
confidence: 99%